Psychology of Colors and Facial Expressions with Application on a CG Short Clip - Steinert, Paulina
Nature is known for being rich in color. Throughout evolution, humankind’s brains have learned to respond to selected colors in multiple ways by assigning meanings to them. Since colors have an impact on our perception of the world, they can be artificially integrated into the media world in order to trigger thought processes. The media world utilises them as powerful tools to create impressions. This study aims to determine the natural and artificial occurrence of different hues in wildlife and their use in character/environment design. This thesis’ practical part uses the gathered information and integrates it actively into the short clip’s character design in rela- tion to its non vocal communication. The methods of choice for the research were literature, studies, films, online articles, and analy- ses that addressed the topics of color psychology and non-verbal/vocal communication. The results suggest that an even wider range of color palettes can be implemented into media to create more advanced stunning motion pictures, although there already are very stereotypical schemes that can be relied on but should not.
Keywords: CG; Design; Color Effects; Body Language; Animation